Current Strategies in Prevention of Postoperative Infections in Spine Surgery. Issue 2 (April 2020) - Atesok, Kivanc; Papavassiliou, Efstathios; Heffernan, Michael J.; Tunmire, Danny; Sitnikov, Irina; Tanaka, Nobuhiro; Rajaram, Sakthivel; Pittman, Jason; Gokaslan, Ziya L.; Vaccaro, Alexander; Theiss, Steven
Study Design: Narrative review. Objectives: Postoperative surgical site infections (SSIs) are among the most common acute complications in spine surgery and have a devastating impact on outcomes. They can lead to increased morbidity and mortality as well as greater economic burden. Hence, preventive strategies to reduce the rate of SSIs after spine surgery have become vitally important. The purpose of this article was to summarize and critically analyze the available evidence related to current strategies in the prevention of SSIs after spine surgery. Methods: A literature search utilizing Medline database was performed. Relevant studies from all the evidence levels have been included. Recommendations to decrease the risk of SSIs have been provided based on the results from studies with the highest level of evidence. Results: SSI prevention occurs at each phase of care including the preoperative, intraoperative, and postoperative periods. Meticulous patient selection, tight glycemic control in diabetics, smoking cessation, and screening/eradication of Staphylococcus aureus are some of the main preoperative patient-related preventive strategies. Currently used intraoperative measures include alcohol-based skin preparation, topical vancomycin powder, and betadine irrigation of the surgical site before closure. Postoperative infection prophylaxis can be performed by administration of silver-impregnated or vacuum dressings, extended intravenous antibiotics, and supplemental oxygen therapy. Conclusions: Although preventive strategies are already in use alone or in combination, further high-level research is required to prove their efficacy in reducing the rate of SSIs in spine surgery before evidence-based standard infection prophylaxis guidelines can be built.